Knowledge Engineering and the Semantic Web 4th International Conference, KESW 2013, St. Petersburg, Russia, October 7-9, 2013. Proceedings - Klinov, Pavel; Mouromtsev, Dmitry; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 4th Conference on Knowledge Engineering and the Semantic Web, KESW 2013, held in St. Petersburg, Russia, in October 2013. The 18 revised full papers presented together with 7 short system descriptions were carefully reviewed and selected from 52 submissions. The papers address research issues related to knowledge representation, semantic web, and linked data.
Knowledge representation -- Semantic Web -- Linked data.
Keywords: Computer science; Database management; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Database Management; User Interfaces and Human Computer Interaction